2019
DOI: 10.1002/nop2.404
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effects of empathy on the association between nursing professional values and professional quality of life in Chinese female nurses: A cross‐sectional survey

Abstract: AimThis study aimed to examine whether and to what extent, empathy mediates the association between nursing professional values and professional quality of life (ProQOL) in Chinese female nurses.DesignCross‐sectional study design.MethodsA convenience sample of 733 nurses from Xi'an, Shaanxi Province, China, was recruited. Each participant was invited to complete a self‐administrated socio‐demographic questionnaire, the Nursing Professional Values Scale, the Jefferson Scale of Empathy and the Professional Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…It was also revealed that, higher empathy significantly contributed to higher CS, and lower CF (burnout and STS) in NGNs, which are similar to the results of previous studies on experienced nurses [ 15 , 16 ]. Empathy represents a caregiver’s ability to understand and share in clients’ thoughts and feelings from their perspectives, which can help identify clients’ needs, provide needs-based care, and facilitate clients’ satisfaction [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It was also revealed that, higher empathy significantly contributed to higher CS, and lower CF (burnout and STS) in NGNs, which are similar to the results of previous studies on experienced nurses [ 15 , 16 ]. Empathy represents a caregiver’s ability to understand and share in clients’ thoughts and feelings from their perspectives, which can help identify clients’ needs, provide needs-based care, and facilitate clients’ satisfaction [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, regarding the association between empathy and professional quality of life in nurses, it was found that, empathy was the main etiology for CF [ 14 ]. Empathy was positively and significantly related to CS, but negatively and significantly related to CF among nurses in China and Portugal [ 15 , 16 ]. Furthermore, empathy was a significant contributor to CS in oncology nurses [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The indirect effect of stress on burnout with CS as the mediator is greater than the indirect effect of stress on burnout with STS as the mediator ( indirect 1indirect Based on a nationwide representative sample, the average burnout score of Korean nurses was 26.7 (5.2) indicating moderate burnout. In previous studies-that used the same measurement tool as this studythe average burnout score for American nurses was 23.66-25.63 which was lower than in Korea [21][22][23], while the average burnout score of Chinese nurses was 26, similar to that of Korea [34]. In this study there were 56% of nurses who were rotational shift workers and 88% who did overtime; however, they received a substantially lower annual salary and the results were similar to other Asian countries [20,35].…”
Section: The Parallel Multiple Mediator Modelmentioning
confidence: 49%
“…In particular, the indirect effect of CS was greater than the indirect effect by STS (Table 3) resulting in reducing burnout of nurses. Moreover, high empathy reduces a nurse's burnout [34], which can be interpreted as more positive effects experienced by nurses who feel rewarded by helping others even in di cult situations. Therefore, it would be effective to establish a management strategy to reduce the burnout of nurses in a way that reduces stress and increases CS.…”
Section: The Parallel Multiple Mediator Modelmentioning
confidence: 99%
“…[ 18 ] As there is greatly difference of the healthcare delivery system between China and Western countries, and additionally, although several studies have explored the prevalence and factors of compassion fatigue among various specialty units of the hospital, the results presented by various studies are not completely consistent and even in contradiction. [ 16 , 19 21 ] Thus, the purpose of the present study was to conduct a systematic review and meta-analysis to provide a comprehensive evaluation of current empirical evidence for the prevalence and factors of compassion fatigue among Chinese clinic nurses.…”
Section: Introductionmentioning
confidence: 99%